2022
DOI: 10.3390/ijms232314729
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Blood Flow in Predator Stress-Resilient and -Susceptible Rats and Mechanisms of Resilience

Abstract: Stress-induced conditions are associated with impaired cerebral blood flow (CBF) and increased risk of dementia and stroke. However, these conditions do not develop in resilient humans and animals. Here the effects of predator stress (PS, cat urine scent, ten days) on CBF and mechanisms of CBF regulation were compared in PS-susceptible (PSs) and PS-resilient (PSr) rats. Fourteen days post-stress, the rats were segregated into PSs and PSr groups based on a behavior-related anxiety index (AI). CBF and its endoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 86 publications
(127 reference statements)
0
5
0
4
Order By: Relevance
“…It is well-known that the NAc is a dopaminergic nucleus. In our experimental model of PTSD, we previously observed a decrease in DA concentration in some brain regions, such as the hippocampus and hypothalamus [ 20 , 40 ]. Recently, it has been demonstrated that decreased DA concentration in the brain in PTSD-susceptible rats is associated with a reduction in cerebral blood flow [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well-known that the NAc is a dopaminergic nucleus. In our experimental model of PTSD, we previously observed a decrease in DA concentration in some brain regions, such as the hippocampus and hypothalamus [ 20 , 40 ]. Recently, it has been demonstrated that decreased DA concentration in the brain in PTSD-susceptible rats is associated with a reduction in cerebral blood flow [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our experimental model of PTSD, we previously observed a decrease in DA concentration in some brain regions, such as the hippocampus and hypothalamus [ 20 , 40 ]. Recently, it has been demonstrated that decreased DA concentration in the brain in PTSD-susceptible rats is associated with a reduction in cerebral blood flow [ 40 ]. Low DA levels are generally associated with an increased risk for PTSD, and this state is genetically predetermined [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, metabolic disorders are often associated with the impairment and loss of dopaminergic function [ 79 ]. Predator-induced stress affects the levels of brain dopamine, which are decreased in rats exposed to predator stress [ 80 , 81 ]. Since the w 1118 strain has reduced dopaminergic activity, the interconnected serotonin and dopamine pathways should be studied simultaneously in predator-induced stress.…”
Section: Discussionmentioning
confidence: 99%
“…Control rats were housed under similar conditions for the same period under stress-free conditions. This experimental model of PTSD was developed by Cohen [ 14 ] and has been used in many subsequent studies of experimental PTSD [ 12 , 13 ]. The model is based on the well-known fear response of rodents to a predator and its smell.…”
Section: Methodsmentioning
confidence: 99%
“…Predator stress is considered a well-validated animal model for post-traumatic stress disorder (PTSD) [ 11 , 12 , 13 , 14 , 15 ]. Following PS exposures, rats can be segregated into high anxiety (HA) and low anxiety (LA) phenotypes [ 16 ].…”
Section: Introductionmentioning
confidence: 99%